2017
DOI: 10.19183/how.24.1.303
|View full text |Cite
|
Sign up to set email alerts
|

Using a Systemic Functional Genre-Based Approach to Promote a Situated View of Academic Writing Among EFL Pre-service Teachers

Abstract: This article reports partial results of a qualitative study which explored the gains and challenges encountered by two groups of English as a foreign language pre-service teachers from a public university in Medellin, Colombia, in developing a situated view of academic writing through a systemic functional genre-based instructional unit. The unit was part of a written communications course and used an approach called the teaching-learning cycle. Results from the study suggest that one of the main gains was rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 12 publications
1
16
0
1
Order By: Relevance
“…These findings are consistent with those of other studies such as the ones conducted by Fenwick (Zhang, 2018), and at times even resistant to their complexity (de Oliveira & Avalos, 2018;Correa & Echeverri, 2017), and the need to give them time and sustained support. They also echo results from Gebhard et al (2013) in the sense that they confirm that psts' conceptualizations of grammar not only do shift through time, as psts get engaged in the different text analysis and production activities that usually make part of these language courses, but become more functional and situated.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These findings are consistent with those of other studies such as the ones conducted by Fenwick (Zhang, 2018), and at times even resistant to their complexity (de Oliveira & Avalos, 2018;Correa & Echeverri, 2017), and the need to give them time and sustained support. They also echo results from Gebhard et al (2013) in the sense that they confirm that psts' conceptualizations of grammar not only do shift through time, as psts get engaged in the different text analysis and production activities that usually make part of these language courses, but become more functional and situated.…”
Section: Discussionsupporting
confidence: 91%
“…However, very little is being done in terms of incorporating these theories to efl tp. In fact, the only three studies reported by the literature on the use of sfl with this population are those conducted by Correa & Echeverri (2017), García et al (2014), and Nieto-Cruz (2019). Of these, the only one that reports on results obtained during a grammar course is the one by Nieto-Cruz (2019).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…When it comes to the contribution of genre-based approach in EFL instruction, there have been a great number of previous studies focusing on the use of GBA in teaching the basic linguistic skills, particularly in teaching writing (Nagao, 2018;Correa & Echeverri, 2017;Burgos, 2017;Dirgeyasa, 2016;(Sabouri, et.al., 2014), reading (Adelnia & Salehi, 2016;Sadeghi, et.al., 2013), listening (Cahyono, 2017). Similar to other basic skills, some researchers such as Rifpriyandi & Sudartini (2017), Khatibi (2014), Hapsari (2017), and Rivera (2014) have also shown that the implementation of genre-based approach may positively affect the EFL students' speaking and communicating skill.…”
Section: Introductionmentioning
confidence: 99%